HUBUNGAN KETERAMPILAN MEMBACA APRESIATIF DENGAN KETERAMPILAN MENULIS CERPEN SISWA KELAS X SMA PEMBANGUNAN LABOLATORIUM UNP - Ella, Ella; Thahar, Harris Effendi; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this research is (1) to describe appreciative reading skill, (2) to describe the skill of writing short story, and (3) to analyze the relationship of appreciative reading skill with the skill of writing short story of grade X of SMA UNP Development Labolatorium. The data of this research is the score of reading skill test of apresiatif and score of skill writing writing skill test result. The findings of this research are (1) appreciative reading skill is in good qualification with average score 80,82, (2) skill of writing short story is in good qualification with average value 78,53, and (3) based on t test, H1 is accepted because thitung> ttable is 0.345 > 1.68. Kata kunci       : hubungan, membaca apresiatif, menulis cerpen